2018
DOI: 10.1063/1.5011783
|View full text |Cite
|
Sign up to set email alerts
|

Structural, magnetic, and ferroelectric properties of T-like cobalt-doped BiFeO3 thin films

Abstract: We present a comprehensive study of the physical properties of epitaxial cobalt-doped BiFeO3 films ∼50 nm thick grown on (001) LaAlO3 substrates. X-ray diffraction and magnetic characterization demonstrate high quality purely tetragonal-like (T′) phase films with no parasitic impurities. Remarkably, the step-and-terrace film surface morphology can be fully recovered following a local electric-field-induced rhombohedral-like to T′ phase transformation. Local switching spectroscopy experiments confirm the ferroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…The clear atomic steps in a representative topography image in Fig. 1a show a high-quality surface of the thin film and no R-like striped domains are found, consistent with previous studies on similar films 44,45 . Figure 1b presents the corresponding IP piezoresponse force microscopy (PFM) phase image.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The clear atomic steps in a representative topography image in Fig. 1a show a high-quality surface of the thin film and no R-like striped domains are found, consistent with previous studies on similar films 44,45 . Figure 1b presents the corresponding IP piezoresponse force microscopy (PFM) phase image.…”
Section: Resultssupporting
confidence: 90%
“…Figure 1b presents the corresponding IP piezoresponse force microscopy (PFM) phase image. The striped IP domains oriented along <110> -type directions indicate a monoclinic structure (M c ) [46][47][48] , in agreement with previous X-ray diffraction (XRD) reciprocal space mapping (RSM) data 44 . In Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The large elongation in the [001] direction of T‐like BFO strongly depresses the antiferromagnetic Néel temperature [ 68,171 ] and gives rise to a rich array of structural and/or ferroelectric phase transitions just above room temperature. Various studies have confirmed the presence of G‐type AFM order with a wFM moment, [ 66,265 ] with one study suggesting the coexistence of G‐type and C‐type AFM order, [ 254 ] possibly caused by a weakening of the exchange coupling in the [001] direction. With regard to the cycloid, despite various efforts by neutrons and CEMS, clear evidence of the existence of a long period modulation is still forthcoming.…”
Section: Perturbations To the Cycloidmentioning
confidence: 94%
“…This section would not be complete without reminding the reader that BFO exhibits very rich strain diagrams, most emphatically shown by the formation under strong compressive strain of a giant axial ratio ( c / a ≈ 1.25) tetragonal‐like polymorph, T‐like BFO. [ 65–68,171,265–270 ] In addition to its various interesting piezoelectric, [ 65 ] optical, [ 64 ] and magnetoelectric facets, [ 67 ] T‐like BFO has an intriguing antiferromagnetic structure. [ 11 ]…”
Section: Perturbations To the Cycloidmentioning
confidence: 99%